A geospatial database of drought occurrence in inland valleys in Mali, Burkina Faso and Nigeria - Dossou-Yovo, Elliott Ronald; Kouyaté, A.M.; Sawadogo, T.; Ouédraogo, I.; Bakare, O.S.; Zwart, Sander J. (Elsevier, 2018)
The data described in this article are related to drought occurrence in inland valleys and farmers adaptation strategies. The data were collected in 300 inland valleys distributed in 14 regions of West Africa. The data were collected in two phases. In the first phase, 300 inland valleys were identified in 14 regions and their locations were determined with handheld GPS devices. Questionnaires and informal interviews were administered to inland valleys users to collect data on physical and socio-economic characteristics, hydrology, farmers experience with drought affecting rice production in inland valleys and adaptation strategies. In the second phase, the locations of the inland valleys were imported in a GIS environment and were used to extract additional parameters on soil characteristics and water demand from the Shuttle Radar Topography Mission (SRTM), Africa Soil Information Service (africasoils.net) and POWER database (http://power.larc.nasa.gov). In total, the dataset contains 41 variables divided into seven themes: farmers' experience with drought, adaptive management of rice farmers to drought, physical characteristics, hydrology, management practices, socio-economic characteristics and weather data of inland valleys.